Cyclic Stiffness Modulation of Cell‐Laden Protein–Polymer Hydrogels in Response to User‐Specified Stimuli Including Light. Issue 12 (12th October 2018) - Liu, Luman; Shadish, Jared A.; Arakawa, Christopher K.; Shi, Kevin; Davis, Jennifer; DeForest, Cole A.
Abstract: Although mechanical signals presented by the extracellular matrix are known to regulate many essential cell functions, the specific effects of these interactions, particularly in response to dynamic and heterogeneous cues, remain largely unknown. Here, a modular semisynthetic approach is introduced to create protein–polymer hydrogel biomaterials that undergo reversible stiffening in response to user‐specified inputs. Employing a novel dual‐chemoenzymatic modification strategy, fusion protein‐based gel crosslinkers are created that exhibit stimuli‐dependent intramolecular association. Linkers based on calmodulin yield calcium‐sensitive materials, while those containing the photosensitive light, oxygen, and voltage sensing domain 2 (LOV2) protein give phototunable constructs whose moduli can be cycled on demand with spatiotemporal control about living cells. These unique materials are exploited to demonstrate the significant role that cyclic mechanical loading plays on fibroblast‐to‐myofibroblast transdifferentiation in 3D space. The moduli‐switchable materials should prove useful for studies in mechanobiology, providing new avenues to probe and direct matrix‐driven changes in 4D cell physiology. Abstract : Fusion protein‐based gel crosslinkers that exhibit stimuli‐dependent intramolecular association yield hydrogel biomaterials that undergo reversible stiffening in response to user‐specified inputs. Linkers based on calmodulin yield calcium‐sensitive materials, while those containing the photosensitive light, oxygen, and voltage sensing domain 2 (LOV2) protein give cell‐laden constructs whose moduli can be cycled with spatiotemporal control.